FRI0292 Correlation biomarkers of cartilage and bone turnover with disease activity, ASDAS, function, quality of life, radiology and magnetic resonance imaging in patients with early spondiloarthritis. (23rd January 2014) - Almodovar, R.; Rios, V.; Ocaña, S.; Casas, M.L.; Gobbo, M.; Zarco, P.; Juanola, X.; Mazzucchelli, R.; Quiros, J.
Abstract : Objectives: To determine the relationship between biomarkers and activity, functional capacity, quality of life and radiology in early SpA.To analyse the influence of sex, HLA B27, psoriasis, osteitis in MRI and involvement pattern on biomarkers[matrix metalloproteinase-3 (MMP-3), high sensitivity C-reactive protein (hsCRP), C Telopéptide (CTX) and D-Pyridoline] in early spondiloarthritis (SpA). Methods: A cross-sectional study of baseline visits from 60 patients included in Esperanza program was performed. Patients analyzed were under 45 years old, with onset symptoms within the range of 3 to 24 months.All patients included met the following criteria: a) inflammatory back pain, or b) symmetric arthritis, or c) back pain/articular pain, in addition to at least one of the following: a) psoriasis, b) inflammatory bowel disease, c) anterior uveitis, d) radiographic sacroiliitis, e) family history ofspondylitis, psoriasis, IBD, or AU, f) HLA-B27 positive. Data collected: social/demographic, ESR, CRP, HLA-B27, BASDAI, ASDAS, BASFI, total BASRI and ASQol.MRI of sacroiliac joints (SIJs) was performed on 32 patients and activity was defined according to the ASAS Group definitions for active lesions on MRI. Serum MMP-3 (ELISA), CTX (Cromatogrphic), hsCRP (Nefelometric) and urinary D-pyridoline (QLIA) were measured in all patients. Analysis: Chi square was used to compare rates and U de Mann-Whitney to analyze continuous variables.Pearson correlation coefficient analysis was performed to examine the contribution of differents biomarkers. Results: At baseline, atotal of 60 patients diagnosed of early SpA were included: 26 male (43.3%) and 34 female (56.7%), with age 32.4±6.7 years and disease duracion of 12.4±6.8 months. Twenty two percent of patients had tenían axial affectation, 63.6% peripheral, 4.5% mixed and 9% enthesitic pattern. HLA B27 was positive in 32.6% patients.Twenty two patients (68.7%) had active sacroiliitis by MRI. The values (mean ±SD) were: nocturnal pain (cm) 4.5±2.6; BASDAI (cm) 4.3±2.4; ASDAS 2.2±1.1; ESR (ml/h)14.7±14.6; CRP (mg/L) 5.3±9.4; BASFI (cm) 2.7±2.4; total BASRI 0.68±1.2 and ASQol 6.7±5. CTX (0.53 μgr/L vs. 0.24μgr/L; p=0.001) and MMP-3 (44.3 μgr/L vs. 24.7 μgr/L; p=0.001)were significantly higher in male than in female. CTX (r=0.4, p=0.01)and MMP-3 (r=0.5, p=0.01)showed correlation with arthritis.hsCRPshowed a significant correlation with the ESR level (r=0.3, p=0.04). MMP-3 and urinary D-pyridoline demonstrated a trend toward a positive correlation with ESR (r=0.3, p=0.08) and (r=0.2, p=0.08), respectively. hsCRP showed a trend toward a positive correlation with total BASRI (r=0.4, p=0.05) Conclusions: In our study, the male sex is associated with higher levels of CTX and MMP-3 in early SpA, which may indicate higher radiographic damage in men. Previous papers found correlation between C Telopéptide and MMP-3 with radiographic damage (1, 2). We found significant correlation between CTX and MMP-3 witn arthritis, as a biomarkers reflecting disease activity. References: Maksymowych WP.Arthritis Rheum 2007, 56:1846-53. Vosse D. Rheumatology 2008, 47:1219-22. Disclosure of Interest: R. Almodovar Grant/Research support from: "Esperanza Program has been supported by an unrestricted grant from Pfizer", V. Rios: None Declared, S. Ocaña: None Declared, M. L. Casas: None Declared, M. Gobbo: None Declared, P. Zarco: None Declared, X. Juanola: None Declared, R. Mazzucchelli: None Declared, J. Quiros: None Declared